Heterotopia or overlaying cortex: What about in-between? - Cvetkovska, Emilija; Martins, William Alves; Gonzalez-Martinez, Jorge; Taylor, Ken; Li, Jian; Grinenko, Olesya; Mosher, John; Leahy, Richard; Chauvel, Patrick; Nair, Dileep (Elsevier BV, 2019)
We describe a patient with unilateral periventricular nodular heterotopia (PNH) and drug-resistant epilepsy, whose SEEG revealed that seizures were arising from the PNH, with the almost simultaneous involvement of heterotopic neurons ("micronodules") scattered within the white matter, and subsequently the overlying cortex. Laser ablation of heterotopic nodules and the adjacent white matter rendered the patient seizure free. This case elucidates that "micronodules" scattered in white matter between heterotopic nodules and overlying cortex might be another contributor in complex epileptogenicity of heterotopia. Detecting patient-specific targets in the epileptic network of heterotopia creates the possibility to disrupt the pathological circuit by minimally invasive procedures.